Maimonides and the Merchants - Cohen, Mark R.
1 online resource (247 pages)
Keywords: In Maimonides and the Merchants, Mark R. Cohen reveals the extent of pragmatic revisions to the halakha, or body of Jewish law, introduced by Moses Maimonides in his Mishneh Torah, the comprehensive legal code he compiled in the late twelfth century.